Design of Memory Interface and Programmer for Ferroelectric Random Access Memory (FeRAM) - Praveen J, Vasanth Kumar M, Sreecharan BR, Shruthi IT, Gowda Rachita BV (International Journal of Advanced Science and Technology, 2020)
The on-board computer of the satellite has a PROM which is volatile. PROM in on-board Computers is used to store the Program data for the operation of the various sensors and devices in the satellite [1]. The software requires constant improvisation; using PROM to store the program data is not feasible. A unique approach is proposed to replace PROM in an on-board computer. A Memory interface is designed for the targeted for storing the program data. FeRAM is a non-volatile memory and has faster access time compared to PROM [2]. The memory interface circuit is designed using the OrCAD Capture tool with the proper analysis of power requirements. FeRAM is programmed using the Microsemi smart fusion Board. Libero SoC and Soft Console software are used to program the FeRAM. For embedded systems, being able to run native TCP/IP makes it possible to connect the system directly to an intranet or even the global Internet. FeRAM can be programmed by a remote PC connected to the internet. To authenticate the data, Checksum is verified after writing the data into FeRAM. FeRAM has faster access time compared to PROM and high data retention time. This will make the FeRAM ideal to store the program data.  Keywords: PROM, FeRAM, OrCAD, Micro-Semi, Smart Fusion board.